2013
DOI: 10.1542/peds.2012-3239
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity: Knowledge, Attitudes, and Practices of European Pediatric Care Providers

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Health care professionals face problems managing obesity and often fail to follow guidelines for its management in practice. Only a few singlecountry reports are available describing delivery of primary care to children with obesity. WHAT THIS STUDY ADDS:Nearly all primary pediatric care providers from 4 European countries recognize the importance of obesity in pediatric practice, but only half use BMI clinically, and many lack the confidence and the infrastructure needed for prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 26 publications
2
39
0
3
Order By: Relevance
“…In fact, screening and tracking BMI percentile according to age and encouraging healthy nutrition and physical activity (PA) are recommended but are not universally delivered in pediatric care. [9][10][11] Although most pediatricians want to prevent obesity, few believe there are any effective treatments once a child is overweight. 9 Practitioners often rely on their professional judgment or on adult diagnostic criteria to identify pediatric obesity because they are unaware of, or lack access to, the appropriate diagnostic tools and guidelines.…”
mentioning
confidence: 99%
“…In fact, screening and tracking BMI percentile according to age and encouraging healthy nutrition and physical activity (PA) are recommended but are not universally delivered in pediatric care. [9][10][11] Although most pediatricians want to prevent obesity, few believe there are any effective treatments once a child is overweight. 9 Practitioners often rely on their professional judgment or on adult diagnostic criteria to identify pediatric obesity because they are unaware of, or lack access to, the appropriate diagnostic tools and guidelines.…”
mentioning
confidence: 99%
“…This is supported by a number of authors. [9,10] Goldman, Modan-Moses [9] reported that only 13% of Israeli physicians routinely weighed all children and work in Europe by Mazur, Matusik [10] found only 50.3% of physicians usually calculated children's BMI. Further, Van Gerwen, Franc [11] found only 5% to 33% of clinicians felt competent to manage childhood obesity and Mazur, Matusik [10] reported only 21.4% of physicians felt competent.…”
Section: Introductionmentioning
confidence: 99%
“…[9,11] Health professionals expressed a high interest in more professional education. [10,13,14] Several studies have shown that one of the barriers for health professionals when providing care to overweight/obese children is parent-related factors, such as the possibility that parents may become defensive and food may be seen as nurturing. [8,14,15] The low rate of measuring children's height and weight may be because it is a sensitive topic to discuss with parents, so GPs only weigh children when they are concerned or parents raise the issue.…”
Section: Introductionmentioning
confidence: 99%
“…However, national [10] and international [11][12][13][14] studies have identified obstacles to the implementation of obesity treatment in daily clinical work within primary care. Some of the more common factors described are lack of knowledge [10,13], lack of positive attitude [11][12][13] among the staff working with obese patients, vague guidelines [10,12] and lack of practical descriptions on how to implement the guidelines [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the more common factors described are lack of knowledge [10,13], lack of positive attitude [11][12][13] among the staff working with obese patients, vague guidelines [10,12] and lack of practical descriptions on how to implement the guidelines [12][13][14]. The choice of treatments offered to patients often depends on local conditions or traditions [13].…”
Section: Introductionmentioning
confidence: 99%